BIMBINGAN ABDOMINAL EXERCISE PADA SISWI SEKOLAH MENENGAH PERTAMA DI WILAYAH KERJA PUSKESMAS SUKAWATI II KABUPATEN GIANYAR - Ni Made Dwi Mahayati (Poltekkes Kemenkes Denpasar, 2020)
One sign of adolescent girls' sexual development is the occurrence of menstruation as a sign of the beginning of puberty which can be accompanied by dysmenorrhea. Dysmenorrhea is not a disease but not a few teenage girls use analgesic drugs to reduce pain. Long-term use of drugs can have an impact on the health of young women. Management of dysmenorrhea can be done in a safer, easier and cheaper way, namely by abdominal exercise which is a physical exercise to increase the pain threshold. It is important to increase knowledge and skills in handling dysmenorrhea early to minimize the impact of drug use. The purpose of this community service is to increase the knowledge and skills of junior high school students about abdominal exercise as a treatment for dysmenorrhea.Community service methods are carried out in the form of pretest - guidance - posttest. Guidance on abdominal exercise using media booklet and video given to 42 junior high school students at SMPN 3 Sukawati and Sila Candra Gianyar Middle School in September and October 2019.The results of the guidance show knowledge scores: before being given guidance an average of 65.71 and after receiving guidance an average of 88.57. Skill scores after receiving abdominal exercise guidance averaged 91. It is recommended that socializing abdominal exercise as an alternative to nonpharmacalogical dysmenorrhea treatment. Keywords: abdominal exercise, dysmenorrhea, guidance, knowledge, menstruation